2019
DOI: 10.1002/dvdy.26
|View full text |Cite
|
Sign up to set email alerts
|

Expression of new genes in vertebrate tooth development and p63 signaling

Abstract: Background p63 is an evolutionarily ancient transcription factor essential to vertebrate tooth development. Our recent gene expression screen comparing wild‐type and “toothless” p63−/− mouse embryos implicated in tooth development several new genes that we hypothesized act downstream of p63 in dental epithelium, where p63 is also expressed. Results Via in situ hybridization and immunohistochemistry, we probed mouse embryos (embryonic days 10.5‐14.5) and spotted gar fish embryos (14 days postfertilization) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…SHH was previously shown to be expressed in the embryonic leopard gecko enamel organ (Handrigan and Richman 2010). Cluster 6 cells expressed Fermt1 (Rostampour et al 2019), Irx1 (Yu et al 2017), Ednrb (Neuhaus and Byers 2007) and Itgb4 (Salmivirta et al 1996) all of which are expressed in the mouse enamel organ. Markers of fully functional ameloblasts were not identified in cluster 6, even though these genes were found in the bulk-RNA-seq data for developing teeth.…”
Section: Resultsmentioning
confidence: 99%
“…SHH was previously shown to be expressed in the embryonic leopard gecko enamel organ (Handrigan and Richman 2010). Cluster 6 cells expressed Fermt1 (Rostampour et al 2019), Irx1 (Yu et al 2017), Ednrb (Neuhaus and Byers 2007) and Itgb4 (Salmivirta et al 1996) all of which are expressed in the mouse enamel organ. Markers of fully functional ameloblasts were not identified in cluster 6, even though these genes were found in the bulk-RNA-seq data for developing teeth.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of these variants were identified in genes not previously associated with the ns-TA risk, including CHD7 (OMIM * 608892), CREBBP , EVC (OMIM * 604831), LEF1 (OMIM + 153245), ROR2 (OMIM * 602337), TBX22 (OMIM * 300307) and TP63 . Expression and functional studies have demonstrated that protein products of all these novel candidate genes play crucial roles during odontogenesis and craniofacial development [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Mice deficient in Lef1 , an essential epithelial survival factor in tooth morphogenesis, show arrested tooth development at the late bud stage before forming a mesenchymal dental papilla [ 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A gene regulatory network dominated by p63, which can regulate the adhesion, polarity and migration of odontogenic cells, may exist during the determination period of the dental-forming region. 35 Deficiencies of these transcription factors (Pitx2, Lef1 and P63) inhibit early tooth development, consequently leading to missing teeth. 33,[36][37][38][39][40] The developmental stage subsequent to the laminal stage is the placode stage (Fig.…”
Section: Tooth Region Determinationmentioning
confidence: 99%